Atrial Fibrillation and Dementia. Issue 7 (18th August 2020) - Bunch, T. Jared
Abstract : Atrial fibrillation is associated with multiple adverse comorbidities, including the development of dementia in patients with and without a history of stroke. Mechanistic models have been proposed to explain the association of AF and dementia. Alterations of brain perfusion from embolic events, bleeding, and rhythm-related hypoperfusion underlie many of these models. Multiple mediators such as oxidative injury, inflammatory and autoimmune mechanisms, and genetic predisposition also interplay in the disease association. There are potential therapeutic opportunities to reduce dementia risk, including early and effective use of anticoagulation and strategies to improve brain perfusion through rhythm and rate control approaches. Prospective trials are needed to evaluate these therapeutic opportunities that carefully measure cognitive function and dementia incidence.